The Influence of Taste and Packaging on Purchase Decisions and Repurchase Intentions - Abas Tegar Wijaksono; Meylani Tuti (University of Merdeka Malang, 2024)
The purpose of this study was to determine how taste and packaging influence purchasing decisions and repurchase interest. The population of this study were 271 consumers of Nikita Fried Chicken. By selecting a sample that only includes consumers of Nikita Fried Chicken products, the sampling approach uses purposive sampling. Data validity and trustworthiness have been checked. data analysis methods that combine quantitative and descriptive methods. Analysis using quantitative data is carried out using Structural Equation Modeling (SEM) using smart PLS software. Based on the research, the taste and packaging of Nikita Fried Chicken products have a direct and indirect impact on how customers form purchasing decisions and repurchase intention. This study contributes to increasing purchases through flavor and packaging. This study has implications for researchers and sellers on how to increase sales through flavor and packaging. The obstacle is the number of respondents in this study who are only from the Bekasi area. Create new research tools that use other brands and expand the population to cities other than Bekasi.